Automated, Ultra‐Fast Laser‐Drilling of Nanometer Scale Pores and Nanopore Arrays in Aqueous Solutions. (3rd April 2019) - Gilboa, Tal; Zvuloni, Eran; Zrehen, Adam; Squires, Allison H.; Meller, Amit
Abstract: The ability to quickly and reliably fabricate nanoscale pore arrays in ultra‐thin membranes such as silicon nitride (Si x N) is extremely important for the growing field of nanopore biosensing. Laser‐based etching of thin Si x N membranes immersed in aqueous solutions has recently been demonstrated as a method to produce stable functional pores. Herein, the principal mechanism governing material etching and pore formation using light is investigated. It is found that the process is extremely sensitive to the relative content of Si over N atoms in the amorphous membrane, produced by chemical vapor deposition. Commonly, Si x N membranes are made to be Si‐rich to increase their mechanical stability, which substantially reduces the material's bandgap and increases the density of Si‐dangling bonds. Hence, even minimal batch‐to‐batch variation may lead to remarkably different etch rates. It is shown that higher Si content results in orders of magnitude faster etching rates. This rate is further accelerated in an alkaline environment allowing on‐demand controlled nanopore formation in about 10 s time even at low laser radiation intensities. These results highlight that photoactivation of the Si x N by the incident beam is critical to the chemical etching process and can be used to readily produce nanopore arrays at any specific location. Abstract : Low‐intensity laser etching and nanopore formation in amorphous silicon‐nitride (Si x N) freestanding films is found to be highly dependent on the Si to N ratio. Increasing the relative Si content yields orders of magnitude increases in etch rate, which is further accelerated in alkaline environments, enabling the fabrication of nanopore arrays within tens of seconds at any arbitrary location.